Penilaian Kualitas Kampung Hijau Rawajati Sebagai Kampung Ramah Lingkungan Yang Berkelanjutan - Nadhira Rizky Yanti; Nany Yuliastuti (Teknik PWK (Perencanaan Wilayah Kota), 2019)
awajati Green Village needs to be supported by good quality housing.Functioning Maintenance of housing infrastructure can improve environmental qualityand sustainability of settlements. This research is to assess the quality of Rawajati GreenVillage in an environmentally friendly village concept. After receiving the Kalpataruaward at the DKI Jakarta Provincial level in 2006, can this rawajati green village be ableto support ecological aspects in environmental management. This study uses aquantitative method with descriptive and weighting statistical analysis with a LikertScale. Data was collected through questionnaires for 90 households, interviews withrelevant stakeholders, and field observations. The results of the study on the socialconditions of the community, the economic conditions of the community, relations, andthe ecological settlement environment can be seen that the quality of Kampung HijauRawajati as an environmentally friendly village has not yet fully led to sustainablesettlements. Where the sustainability of Rawajati Green Village is in the moderatecategory with a score of 2.19.